2019
DOI: 10.1007/s11825-019-0236-4
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomes in the DNA era: Perspectives in diagnostics and research

Abstract: Chromosomes were discovered more than 130 years ago. The implementation of chromosomal investigations in clinical diagnostics was fueled by determining the correct number of human chromosomes to be 46 and the development of specific banding techniques. Subsequent technical improvements in the field of genetic diagnostics, such as fluorescence in situ hybridization (FISH), chromosomal microarrays (CMA, array CGH) or next-generation sequencing (NGS) techniques, partially succeeded in overcoming limitations of ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…In the post-genomic era, single-cell cytogenetic (cytogenetic karyotyping) and molecular cytogenetic (FISH) genome analyses are generally considered as outdated techniques with limited applicability [50][51][52]. However, a wide spectrum of changes in the genome behavior at the chromosomal level requires cytogenetic and FISH-based analyses (for further details, see [4,7,28,[45][46][47][48]). Furthermore, FISH-based approaches to interphase chromosomes have already been shown to uncover mechanisms for brain diseases [12,39,53,54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the post-genomic era, single-cell cytogenetic (cytogenetic karyotyping) and molecular cytogenetic (FISH) genome analyses are generally considered as outdated techniques with limited applicability [50][51][52]. However, a wide spectrum of changes in the genome behavior at the chromosomal level requires cytogenetic and FISH-based analyses (for further details, see [4,7,28,[45][46][47][48]). Furthermore, FISH-based approaches to interphase chromosomes have already been shown to uncover mechanisms for brain diseases [12,39,53,54].…”
Section: Discussionmentioning
confidence: 99%
“…chromosome fragility, interphase chromosome breakage, morphological alterations to chromosomes etc.) cannot be appropriately addressed by these technologies developed for studying whole fractions of DNA isolated from large cell populations [4,12,20,[45][46][47]. Taking into account the importance of CIN analysis and the importance of CIN as a biomarker, we suggested that there is a need to reconsider the generally accepted diagnostic approaches to chromosomal abnormalities.…”
Section: An Algorithm For Uncovering Disease Mechanisms Mediated By Cinmentioning
confidence: 99%
“…The applications of FISH-based methods to molecular neurocytogenetic purposes are not limited to detecting chromosomal abnormalities, inasmuch as these may uncover chromosome instability and behavior that are undetectable by single-cell molecular genetic techniques. Even in the post-genomic era, FISH remains an important methodology for human genome analysis [65]. Despite a number of unresolved disadvantages, the resolution of single-cell whole-genome analysis by next-generation sequencing defines this platform as an efficient tool for studying neuronal genomes.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%